Sanitasi Lingkungan dengan Riwayat Pneumonia serta Kontribusinya pada Kejadian Stunting - Dewi, Santika; Pawenang, Eram Tunggul (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: This has become one of the focuses of health problems for health workers and the community considering that the Kedewan sub-district is the westernmost region of the Bojonegoro district which still has difficulty accessing and mobilizing. The purpose of this study was to determine the relationship between environmental sanitation and a history of pneumonia and its contribution to the incidence of stunting. Methods: This type of research is analytic observational with a case control research design. The sample required is a sample of 22 cases and 22 controls.The instruments used are stunting data for the period February-August 2021 at the Kedewan Health Center, questionnaires, and stadiometers. Data analysis was carried out using the Chi-Square test. Results:Tthere was a relationship between latrine ownership and a history of pneumonia in children under five (p-value=0.048), there was a relationship between a history of pneumonia and the incidence of stunting (p-value=0.002). Variables that were not associated with a history of pneumonia were the provision of clean water (p-value=0,632), the condition of the floor of the house (p-value=0,691), and the disposal of garbage (p-value=0,632). Conclusion: The need for increased intervention and monitoring of environmental sanitation from the collaboration of the village government and health centers.